PSYCHOLOGICAL MECHANISMS OF PAIN PERCEPTION AND THEIR MANAGEMENT (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
The article analyzes the psychological mechanisms of pain perception and methods of its management. It is shown that pain is closely related not only to physiological, but also to psychological factors. Based on the biopsychosocial model, the influence of biological, cognitive, emotional and social factors on pain intensity is highlighted. Also, psychological methods such as cognitive-behavioral therapy, relaxation, mindfulness and biofeedback are recommended to reduce pain. The results show the importance of integrating medical and psychological approaches in improving patients' quality of life.